Microwave-accelerated hydrolysis for hydrogen production over a cobalt-loaded multi-walled carbon nanotube-magnetite composite catalyst. (1st March 2023) - Luo, Chunlin; Liu, Shuai; Yang, Gang; Jiang, Peng; Luo, Xiang; Chen, Yipei; Xu, Mengxia; Lester, Edward; Wu, Tao
Graphical abstract: Highlights: Microwave-enhanced catalysis was applied to produce H2 . The HGR increased from 75 to 95.4% under microwave heating. The A under MW irradiation was about 15 folds of conventional heating. The non-thermal effect of microwave irradiation has been proved. The synergistic effect of Co and Fe3 O4 on HGR was verified by DFT calculation. Abstract: Microwave (MW) irradiation is a promising option for the intensification of chemical reaction processes and has been applied in the promotion of many catalytic reactions. Herein, the (CNTs-Fe3 O4 )-Co nanocomposites were designed as microwave-responsive catalysts and was fabricated under a controlled manner. The experimental results showed that MW irradiation can lead to the hydrogen generation rate (HGR) of the (CNTs-Fe3 O4 )(1:4) -Co (10 wt%) catalyst being boosted from 75.0 to 95.4% as compared with conventional heating under the temperature range of 40 to 60℃. Moreover, the evaluation of the catalytic performance of the (CNTs-Fe3 O4 )(1:4) composite with different Co loadings and DFT calculations were carried out to verify the synergistic effect of cobalt and Fe3 O4 sites of the (CNTs-Fe3 O4 )(1:4) -Co (10 wt%) catalyst. Furthermore, the pre-exponential factor (A) of NaBH4 hydrolysis under MW heating was found to be approximately 15 times higher than that of conventional heating, implying that MW irradiation significantly improved the effective collision frequency of the atoms at the reaction interface of the catalyst, resulting in a higher number of active sites on the surface of the (CNTs-Fe3 O4 )(1:4) -Co (10 wt%) catalyst. Additionally, the existence of the non-thermal effect of MW irradiation was studied by using a specially designed experimental set-up. The results showed that MW thermal and non-thermal effects contributed to the enhancement of HGR.